A Pragmatic Approach to Addressing Needs of Crop and Dairy Farming System in the Peri-Urban Area (Indian Journal of Extension Education, 2016)
Increase in the urban population leads to increase in demand for quality food and milk in India. Moreover, the future urbanizing India is greatly depending upon the farming in the fringes of towns and cities to meet its increasing food demand. This has many advantages to the peri-urban crop and dairy farmers. However number of constraints limit the production potential of crop and dairy farming in peri-urban areas. So, the present study was undertaken in peri-urban area of Bengaluru, Karnataka. The identified advantages and constraints pertaining to crop and dairy production system along with suitable strategies were described for further encouragement of peri-urban farming. Findings indicate that additional source of income, remunerative price for milk, high demand for fresh milk were found to be the major advantages of periurban dairy production system. In crop production system, easy market access to farm produce, less cost in transportation of farm produce and huge demand for fresh fruits, vegetables and flowers were the major advantages in peri-urban. Major constraints in practicing peri-urban dairy farming were; increase in frequency of disease incidence in dairy animals, non availability of fodder in time and insufficient land availability for fodder production. Non-availability of irrigation water, non-availability of labour for farm work and increase in labour cost in peri-urban region were reported as serious constraints in peri-urban area of Bengaluru region.